2014
DOI: 10.1017/thg.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

Is the Relationship Between Binge Eating Episodes and Personality Attributable to Genetic Factors?

Abstract: Aspects of disordered eating and personality traits, such as neuroticism are correlated and, individually, heritable. We examined the phenotypic correlation between binge eating episodes and indices of personality (neuroticism, extraversion, openness to experience, agreeableness, conscientiousness and control/impulsivity). For correlations ≥ |0.20|, we estimated the extent to which genetic and environmental factors contributed to this correlation. Participants included 3446 European-American same-sex female tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
12
0
3
Order By: Relevance
“…Previous studies of clinical samples found neuroticism to be a risk factor for binge eating episodes (Koren et al, 2014) and found significant associations between neuroticism and other risk and maintenance factors for binge eating (e.g., low interpersonal esteem and depressive affect) (Mackinnon et al, 2011; Sherry & Hall, 2009). Our findings extend the literature by showing an association between neuroticism and binge eating in the general U.S. adolescent population.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies of clinical samples found neuroticism to be a risk factor for binge eating episodes (Koren et al, 2014) and found significant associations between neuroticism and other risk and maintenance factors for binge eating (e.g., low interpersonal esteem and depressive affect) (Mackinnon et al, 2011; Sherry & Hall, 2009). Our findings extend the literature by showing an association between neuroticism and binge eating in the general U.S. adolescent population.…”
Section: Discussionmentioning
confidence: 98%
“…Behavioral genetic research examining negative emotionality/neuroticism-disordered eating associations has been somewhat mixed. Two studies found that genetic factors largely explained the covariation between negative emotionality/neuroticism and disordered eating symptoms (i.e., binge eating, body dissatisfaction, weight preoccupation, compensatory behavior) in adolescent and young adult females, with genetic correlations (i.e., r a; see definition in Table 1) ranging from .37 to .49 across studies (Klump et al, 2002;Koren et al, 2014). Both studies reported significant non-shared environmental correlations for these personality traits and binge eating (r e 's = .25-.28), whereas Klump et al (2002) did not detect environmental overlap for weight preoccupation, body dissatisfaction, or compensatory behavior.…”
Section: Negative Emotionality/neuroticismmentioning
confidence: 99%
“…They are also more sensitive to criticism; they experience higher levels of rejection; and they have lower self-esteem [51]. In prior research, neuroticism has been connected to the increased drive for thinness in women [52,53], to heightened food and body preoccupation [54], to body dissatisfaction [55], to the self-regulation of eating attitudes (e.g., food temptation) [56], and even to eating disorder diagnosis [48,57] and binge eating [58,59]. According to Fischer, Schreyer, Coughlin, Redgrave, and Guarda [52], the facets of neuroticism, including irritability and difficulty with emotional regulation, are risk factors for developing an ED.…”
Section: Neuroticismmentioning
confidence: 99%